A REGIONAL RE-AUDIT OF THE SYMPTOMATIC MANAGEMENT OF NAUSEA & VOMITING IN THE MEDICAL MANAGEMENT OF MALIGNANT BOWEL OBSTRUCTION. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Jackson, Timothy; Waterman, David; Ahamed, Ashique; Lennon, Rebecca; Suman, Julie; Murray, Yvonne; Brady, Denise; Harrison, Sophie
Abstract : Background: The medical management of symptoms associated with malignant bowel obstruction remains a clinical challenge in palliative care. Where surgical intervention is not appropriate, thorough clinical assessment should guide treatments for nausea and vomiting. In 2011, the North West Palliative Care Regional Audit Group (NWAG) coordinated a multi-centre review revealing variations in prescribing practice and adherence to guidelines. In response, participating organisations were asked to develop action plans. Aim: To re-audit the assessment and medical management of nausea and vomiting in malignant bowel obstruction against updated evidence-based standards, and compare results with the 2011 NWAG audit. Method: A regional, multi-centre, retrospective case note audit was undertaken for patients with malignant bowel obstruction. 8 audit standards were produced following an updated literature review. Data was submitted electronically and analysed centrally by NWAG for participating organisations. Results: Thirteen organisations returned 101 data collection forms (6 hospices, 7 hospitals), an identical number to the original audit. Presence or absence of nausea, vomiting and colic was documented at initial assessment in 77%, 94% 68% respectively (n=101) compared with 80%, 91%, 80% in the original audit. Antiemetics were prescribed via non-oral routes in patients with nausea and/or vomiting in 87% (originally 97%). Where nausea and/or vomiting occurred due to bowel obstruction, regular or continuous non-oral medications were subsequently prescribed within 48hrs in 64% of cases (originally 68%). During an initial 4 day assessment period, if patients required two or more PRN medications for nausea and vomiting in 24 hours, medications were reviewed in 91%. Metoclopramide, if prescribed, was discontinued if colic occurred in 67% of cases. Metoclopramide and cyclizine were prescribed concurrently in 9%. Conclusion: Whilst this re-audit demonstrates some variation from the original audit, practice was consistent in many areas. Findings support the need for regular and comprehensive clinical assessment in order to maintain effective symptom control.